PENGARUH KEPUASAN KERJA, KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP RETENSI KARYAWAN PADA MASA PANDEMI COVID-19 - Ariawangsa, Denick; Mujiati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024, 2024)
Some of the factors that make employees have to resign from the company include cultural differences that are applied by the company, the tasks obtained are not in accordance with their abilities, facilities that are deemed not commensurate with the tasks given, and the compensation given is not commensurate with what is done. This study aims to determine the effect of job satisfaction, compensation, and organizational culture on employee retention. This research was conducted at Natya Hotel Kuta Badung with the number of samples used as many as 36 respondents, using the saturated sampling method and data collection was carried out through interviews and distributing questionnaires. The data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that job satisfaction has a significant effect on employee retention at Natya Hotel Kuta Badung, compensation has a significant effect on employee retention at Natya Hotel Kuta Badung, and organizational culture has a significant effect on employee retention at Natya Hotel Kuta Badung. Theoretically, this research also provides an understanding that by increasing job satisfaction, compensation, and organizational culture, it will be able to retain employees to stay in the company.